Diskussion ved Udstillingen af Exportost paa Landbohøjskolen d. 14de Decbr. 1877. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Diskussion ved Udstillingen af Exportost paa Landbohøjskolen d. 14de Decbr. 1877.